Time trends in cancer risk and pesticide exposure, a long-term follow-up of Danish gardeners - Hansen, Eva S.; Lander, Flemming; Lauritsen, Jens M. (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'Occupational exposure to petrochemical pesticides was high during the first 10–15 years after their introduction in the late 1940s, and, during these years, many cases of intoxication occurred. In the 1960s, the use and marketing of pesticides was regulated to reduce exposure to these substances, and, since 1970, substantial exposure has been rare in Denmark. The present study aimed at investigating the extent to which these alterations have influenced the cancer risk of gardeners. ' ' METHODS ': 'A historical cohort of 3156 male gardeners was followed from May 1975 until 2002 with regard to cancer incidence. ' ' RESULTS ': 'The cancer incidence was significantly below the national average [standardized incidence ratio (SIR) 0.86, 95% confidence interval (95% CI) 0.79–0.94], but an analysis by birth cohort indicated marked differences with a downward tendency for younger birth cohorts. Among the gardeners born prior to 1915, significant increases were found for leukemia (12 cases, SIR 2.33, 95% CI 1.32–4.10) and soft tissue sarcoma (3 cases, SIR 5.87, 95% CI 1.89–18.20). ' ' CONCLUSIONS ': 'Gardeners constitute a healthy worker group, but an increased risk of soft tissue sarcoma and leukemia is indicated for people born prior to 1915, a finding that may reflect substantial pesticide exposure during the late 1940s and the 1950s. Among the gardeners born in 1915 or later, no excess cancer risk was found. The latter finding suggests a cancer-preventive effect for safety recommendations and improved technical devices with respect to pesticide application, along with legislative control measures to reduce pesticide exposure.
Keywords: cancer risk; Denmark; gardener; leukemia; long-term follow-up; pesticide exposure; soft tissue sarcoma; time trend